2018
DOI: 10.1186/s13223-018-0268-3
|View full text |Cite
|
Sign up to set email alerts
|

Rhinosectan® spray (containing xyloglucan) on the ciliary function of the nasal respiratory epithelium; results of an in vitro study

Abstract: BackgroundTo assess the effects of Rhinosectan® spray, a medical device containing xyloglucan, on nasal ciliary function (in MucilAir™Nasal cells).MethodsMucilAir™Nasal, a three-dimensional organotypic airway tissue model (with different cell types), was treated with Rhinosectan® (30 µl) or with a control (saline solution). The effects of Rhinosectan® were evaluated at 15 and 60 min post-exposure by: measurement of the cilia beating frequency (Hz), mucin detection (Enzyme-Linked Lectin Assay—ELLA), mucociliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Topical application of heat-killed bacteria could have also a role in the management of allergic respiratory diseases, based on the favorable results obtained with mucosal protectors in nasal in vitro models [142,144].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical application of heat-killed bacteria could have also a role in the management of allergic respiratory diseases, based on the favorable results obtained with mucosal protectors in nasal in vitro models [142,144].…”
Section: Discussionmentioning
confidence: 99%
“…The protective properties of tyndallized probiotics plus other mucosal protectors, such as xyloglucan, should deserve further research, in intestinal cells and also in other models, as nasal epithelial cells, based on the previous studies supporting the use of xyloglucan as protector of the nasal mucosal epithelial cells [143,144]. In fact, xyloglucan in nasal formulations is an innovative strategy for the management of nasal disorders, as rhinitis and rhinosinusitis, based on their protective properties on the nasal epithelial cells, maintaining the barrier integrity and allowing the avoidance of allergens and triggering factors, as demonstrated in MucilAir™Nasal cells [4,143,144] and in patients with rhinosinusitis [145].…”
Section: Protective Barrier Properties Of Tyndallized Probiotics Imentioning
confidence: 99%
“…In spheroids, vascularization and cellular crosstalk are particularly relevant [60]. Reconstructed tissues/ex vivo samples are used to assess cilia beating frequency, mucus production, airway surface liquid volume, mucociliary clearance [61]. Effects on alveolar macrophages can be assessed by measuring of chemotaxis, phagocytosis and phospholipidosis [62].…”
Section: Readout Parameters Of In Vitro Studiesmentioning
confidence: 99%
“…An in vitro study that used a three-dimensional organotypic airway tissue model (with different cell types) treated with XG, showed that the application of XG to nasal epithelial cells did not impair ciliary movement, enhanced mucociliary clearance and facilitated phagocytosis while reducing mucin secretion, properties which are favorable for the management of rhinitis and associated conditions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%